Blood mercury levels and fish consumption in pregnancy: Risks and benefits for birth outcomes in a prospective observational birth cohort - Taylor, Caroline M (Int J Hyg Environ Health, 2016)
BACKGROUND: To avoid exposure to mercury, government advice on fish consumption during pregnancy includes information on fish species to avoid and to limit, while encouraging consumption of least two portions of fish per week. Some women may, however, chose to avoid fish completely during pregnancy despite potential benefits to the fetus. OBJECTIVES: Our aims were to evaluate the effects of blood mercury levels in pregnant women on birth outcomes in the UK, and to compare outcomes in those who ate fish with those who did not. METHODS: Pregnant women were enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC). Whole blood samples for singleton pregnancies with a live birth were analysed for Hg by inductively coupled plasma dynamic reaction cell mass spectrometry (n = 4044). Fish intake was determined by a food frequency questionnaire during pregnancy. Data collected on the infants included anthropometric variables and gestational age at delivery. Regression models were adjusted for covariates using SPSS v23. RESULTS: There were no significant associations of maternal blood Hg level with birthweight, head circumference or crown–heel length in adjusted linear regression models. Similarly, there were no increased odds of low birthweight or preterm delivery in adjusted logistic regression models. When the models were repeated after stratification into fish-eaters and there were no associations except for a negative association with birthweight in non-fish-eaters (unstandardised B coefficient −58.4 (95% confidence interval −113.8, −3.0) g, p = 0.039). CONCLUSION: Moderate mercury levels in pregnancy were not associated with anthropometric variables, or on the odds of low birthweight or preterm birth. Fish consumption may have a protective effect on birthweight. Consumption of fish in line with government guidelines during pregnancy should be encouraged.